Evaluation of the prevalence of musculoskeletal disorders in nurses: A systematic review - Soylar, Pinar; Özer, Ali (My University, 2018)
Nurses exposure many risk factors in the hospital setting. Musculoskeletal disorders (MSDs) is a common health problem between work related disabilities and injuries in nurses. The aim of this review was to examine the prevalence of MSDs in nurses and also summarize risk factors, outcomes, solutions. An electronic search was conducted in Pub Med in January 2017. Publications in the last ten years were researched using the key words: “Work Related Musculoskeletal Disorders” and “Nurses”. The initial electronic search identified 111 papers. Some articles were excluded since they were not related to our study topic (7 articles were review, 15 of them were related to the roles of nurses in some musculoskeletal disorders, 14 articles were about nurses who working outside the hospital or new graduated/student, 28 articles addressed work related other health problems, 3 of them were related to hospital ergonomics and risk factors and 7 articles were interventions studies). Three papers were not reached to full text or abstract. The total number of remaining articles was 34 and all of them were included the study. It was considered that reported musculoskeletal disorders in nurses were limited to the past 12 months. It had been found that the prevalence of MSDs varied between 33.0% and 88.0%. The most commonly affected body regions were lower back, shoulder, neck, knees, wrists/hands. Lower back pain complaints were found to vary between 49.0% and 84.0%. The findings indicated that the work related musculoskeletal disorders associated with cumulative trauma and repetitive tasks included: lifting, transferring or repositioning, prolonged standing and also awkward postures (stooping, bending and reaching). These work-related health problems in nurses were significantly associated with age, gender, body mass index, ward, shift working and working in a hospital. Studies showed that musculoskeletal disorders were most seen among the operation room nurses and intensive care nurses. Also, MSDs were found to be the main causes of absenteeism, demanding a change of duty or job and visiting a physician. The MSDs was more prevalent occupational health problem among nurses. The prevalence of MSDs was associated with both demographic characteristics of nurses and hospitals’ organizational factors. It was confirmed that making ergonomics interventions could improve the working environment in the hospital.
Keywords: Hemşirelik